2012
DOI: 10.4102/sajpsychiatry.v18i1.271
|View full text |Cite
|
Sign up to set email alerts
|

Predicting frequency of suicide attempts of adolescent outpatients at Weskoppies Hospital using clinical and demographic characteristics

Abstract: <p>The prevention of suicide, particularly adolescent suicide, remains one of the biggest challenges in psychiatry.</p><p><strong>Objectives. </strong>To ascertain: (i) clinical and demographic characteristics; and (ii) possible associations between these characteristics and suicide attempt frequency in a selected patient group at Weskoppies Hospital over 4 months.</p><p><strong>Methods.</strong> Fifty adolescent outpatients aged between 13 and 17 years wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…One pitfall is the risk of false positives (Horowitz et al, 2009;Nielssen et al, 2017;Ross et al, 2016). This concern may even be exacerbated in a resourceconstrained environment (Fine et al, 2012). Integrating screening for adolescent mental health problems, and in particular screening for risk of suicide, into a wider comprehensive evaluation of a young person´s mental health and social well-being can somewhat reduce the risk of false positives (Harris et al, 2019;Kessler et al, 2020).…”
Section: Recommendationsmentioning
confidence: 99%
“…One pitfall is the risk of false positives (Horowitz et al, 2009;Nielssen et al, 2017;Ross et al, 2016). This concern may even be exacerbated in a resourceconstrained environment (Fine et al, 2012). Integrating screening for adolescent mental health problems, and in particular screening for risk of suicide, into a wider comprehensive evaluation of a young person´s mental health and social well-being can somewhat reduce the risk of false positives (Harris et al, 2019;Kessler et al, 2020).…”
Section: Recommendationsmentioning
confidence: 99%
“…Alonzo and colleagues (2014) studied the impact of parental addiction on children’s risk of suicide attempts in the United States and, after adjusting for sociodemographic and clinical variables such as age, gender, race, educational level, family income, and histories of depression, concluded that parental addiction nearly doubled the likelihood that children would attempt suicide in their lifetimes (9). Similarly, Fine and colleagues’ (2012) research in Pretoria (South Africa) on adolescents with a history of suicide attempts showed that 45% of these adolescents’ caregivers had a history of alcohol abuse and 14% had a history of drug abuse; thus, they reported that a history of alcohol and drug abuse among caregivers in an important predictor of adolescent suicide attempts (10). …”
Section: Introductionmentioning
confidence: 99%
“…While a review of theoretical and empirical works show that researches on depression and its effects on Nigerian students are common, investigations on depression and its effect on suicidality in Nigerian students are, however, not that common. Schlebusch, Burrows and Wada (2009), Palmier (2011), Fine, Alison, Vanderwesthuizen and Kruger (2012), and Norhayati and Suen (2014) reported that researches on suicidality in the developing world are sparse for a number of reasons such as socio-cultural taboos, political and economic instability, cultural and religious diversity and beliefs. In relation to taboo, committing suicide is seen as disgraceful and families of people who commit suicide do not openly come out to verify that a family member has committed suicide.…”
Section: Introductionmentioning
confidence: 99%